Features of School Adaptation of Pupils with Autism Spectrum Disorder in the First Year of Study - Antonova, I.D.; Kostin, I.A. (Klinicheskai͡a︡ i spet͡s︡ialʹnai͡a︡ psikhologii͡a, 2023)
The article discusses the results of the initial stage of a longitudinal study of the school adaptation of children with autism spectrum disorders studying in primary school. The study sample is represented by 78 first-graders with autism spectrum disorder (ASD) who study in 20 schools from 14 Russian regions. The study was based on the method of expert assessments obtained through questionnaires of teachers and parents of students. We used the "Expert assessment of a child's adaptation to school" methodology modified for the needs of the study (V.I. Chirkov, O.V. Sokolova, O.L. Sorokina) and a questionnaire for assessing social skills and behavior of schoolchildren with ASD by L.V. Shargorodskaya. The dynamics of school adaptation of students with ASD was assessed in relation to their personal and educational achievements. By the end of the first year of study, a positive dynamic of the level of school adaptation was found in the sample study. At the same time, educational achievements were more pronounced and personal achievements associated with the expansion of communication opportunities and socialization of children were extremely low. The influence of a number of factors on the school adaptation of children with ASD was revealed, the most significant of which was the factor of children attending correctional classes at preschool age (at least two years). Special school preparation classes (at least one year) and kindergarten attendance at preschool age (at least two years) proved to be significant factors of school adaptation for children with ASD and intellectual disabilities. This sample revealed a negligible impact of remedial classes conducted in the first year of study on the educational results of students with ASD and the absence of the influence of this factor on their personal achievements. Further observation of the group of children included in the study during their primary school education will allow to clarify and supplement the data obtained. В статье обсуждаются результаты начального этапа лонгитюдного исследования школьной адаптации детей с расстройствами аутистического спектра (РАС), обучающихся в младшей школе. Выборка исследования представлена 78 детьми-первоклассниками с РАС, обучающимися в 20 школах из 14 российских регионов. Исследование опиралось на метод экспертных оценок, получаемых с помощью анкетирования педагогов и родителей обучающихся. Использовались модифицированная для нужд исследования методика «Экспертная оценка адаптированности ребенка к школе» (В.И. Чирков, О.В. Соколова, О.Л. Сорокина) и анкета оценки социальных навыков и поведения школьников с РАС Л.В. Шаргородской. Динамика школьной адаптации учащихся с РАС оценивалась применительно к их личностным и образовательным достижениям. У исследуемой выборки к концу первого года обучения обнаружена положительная динамика уровня школьной адаптации. При этом более выраженными оказались образовательные достижения и крайне низкими - личностные, связанные с расширением возможностей коммуникации и социализацией детей. Выявлено влияние ряда факторов на школьную адаптацию детей с РАС, наиболее значимым из которых оказался фактор посещения детьми коррекционных занятий в дошкольном возрасте (не менее двух лет). Специальные занятия по подготовке к школе (не менее одного года) и посещение детского сада в дошкольном возрасте (не менее двух лет) оказались значимыми факторами школьной адаптации для детей с РАС и интеллектуальными нарушениями. На данной выборке выявлено незначительное влияние коррекционных занятий, проводимых на первом году обучения, на образовательные результаты учащихся с РАС и отсутствие влияния данного фактора на их личностные достижения. Дальнейшее наблюдение за группой детей, включенных в исследование, на протяжении их обучения в начальной школе позволит уточнить и дополнить полученные данные.